OC-051 Erk MAP kinase signalling and PEA3 are synergistic in predicting adversity in gastric adenocarcinomas. (23rd September 2015) - Keld, R R; Guo, B; Downey, P; Gulmann, C; Ang, Y; Sharrocks, A
Abstract : Introduction: The PEA3 sub family consists of 3 similar transcription factors, PEA3, ER81 and ERM. In gastric cancer cells PEA3 is activated by H pylori and it has been shown to regulate MMP-7 and invasion. PEA3 mRNA expression correlates with an adverse prognosis in gastric adenocarcinomas. We have previously shown that PEA3 and/or ER81 mRNA correlates with adverse the indicator, MMP-1 and MMP-7. Very high PEA3 protein expression in isolation is associated with tumour metastases. However tumours with PEA3 mRNA and lower protein expression did not correlate with prognostic markers. PEA3 is regulated by ERK MAP kinase signalling in oesophageal adenocarcinomas and we investigated if this pathway plays an important role in gastric adenocarcinomas. Methods: Patients with gastric adenocarcinoma (37) and controls (11) were selected. Tissue microarrays were constructed for immunohistochemical studies of PEA3 and pERK. The t test and chi square test were used for statistical analysis. A p value <0.05 was judged to be significant. Results: In patients with gastric adenocarcinoma, active ERK signalling is present in 60%. From these, ERK signalling is associated with an advanced tumour stage (AJCC stage 1 67%, stage 2: 33%, stage 3: 21% stage 4: 80% p=0.04). Active signalling is present in stage 1 and 2 tumours (55%). Survival is significantly reduced in patients with active ERK signalling (41 vs 34 months P=0.05) on univariate analysis. Adenocarcinomas with PEA3 and pERK co-occurrence frequently have distant metastases 60% (T and N stage vs M stage p=0.048). Survival is worse in patients with combined pERK and PEA3 presence compared to PEA3 or pERK presence in isolation (12 vs 30 vs 63 months p=0.071). Conclusion: Our results indicate that ERK MAP kinase signalling is an important marker of an advanced tumour stage and prognosis in gastric adenocarcinoma. The signalling pathway is frequently active in early stage (AJCC 1–3) tumours. Previous studies have shown poor results with MEK inhibition treatment in Pancreatic, Colon, Lung and Breast cancers. This may be due to the selection of heterogeneous tumours with an advanced disease stage or tumours with activation of alternative signalling pathways. Our results suggest consideration of trialling MEK inhibition treatment in patients with earlier stage disease in gastric adenocarcinoma. The more adverse outcome in patients with the combination of ERK MAP signalling and PEA3 indicates that a combined approach with inhibition of PEA3, could be considered in selected patients.